Public Administration in Bukhara Khanate - Avalova Gulshod (Periodica Journal, 2022)
National values are inextricably linked with the nation's naturalhistorical development, social life, way of life, past, future, culture, spirituality, customs, traditions, language, the region where it was created, etc. This article talks about state administration in Bukhara Khanate
Keywords: thinker; Historical; Shaybani; Movarounnahr